Управління параметрами QoS мультисервісної мережі з комутацією віртуальних каналів на основі розподілу запасу ресурсів - Лаврів, О.А.; Бугиль, Б.А. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
There is a problem of network resource management to ensure the required level of QoS due to the rapid development and implementation of multiservice networks on bases of virtual channel switching. A way to manage bandwidth and network delays based on the distribution of stocks is proposed.